Efficacy and safety of oral misoprostol solution compared to sublingual misoprostol for induction of labor at term pregnancy - Ripa, Halima Jahan; Akhter, Dilruba; Haque, Murshidul; Ahmed, Naorin; Nesa, M. Karimatun; Fatema, M. Muhtarema; Haider, Chowdhury Afsana; Akter, M. Farhana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Induction of labor (IOL) is the artificial stimulation of uterine contractions at term to achieve vaginal delivery. This study aimed to compare the efficacy and safety of 25 μg oral versus sublingual misoprostol for labor induction at term pregnancy. The aim of the study was to compare the efficacy and safety of oral misoprostol solution versus sublingual misoprostol for induction of labor in term pregnancies. Methods: This randomized controlled trial was conducted at the Department of Obstetrics and Gynecology, Institute of Child and Mother Health (ICMH), Matuail, Dhaka, Bangladesh, from July 2023 to June 2024, including 66 term pregnant women with a singleton cephalic fetus and unfavorable cervix (Bishop score <6). Participants were randomized to oral misoprostol solution (Group A, n=33) or sublingual misoprostol (Group B, n=33), with labor progress, maternal, and neonatal outcomes monitored. Data were analyzed using SPSS v26, with P<0.05 considered significant. Results: Among 66 term women (33 oral, 33 sublingual), most were 20-30 years, housewives, with normal BMI and primigravida. Indications and gestational age were similar. Oral group required higher misoprostol doses (3.6±1.1 vs. 3±1.9, p=0.010), but labor times, oxytocin use, Bishop score improvement, delivery mode (vaginal 72.7% vs. 75.8%), neonatal outcomes, and adverse effects were comparable. Success rates were 84.8% vs. 90.9%. Conclusions: Both oral and sublingual misoprostol are similarly effective for labor induction, with oral misoprostol showing a slightly safer profile.